Escritura(s). Borde(s). Arte(s) - Rodríguez, Claudia María del Valle; Galante, María Luz; Pietro, Ana Paula; Matarozzo, Ornella (Facultad de Artes, 2022)
Fil: Rodríguez, Claudia María del Valle. Universidad Nacional de Córdoba. Facultad de Artes; Argentina.